First report of morbilliviral encephalitis in an adult striped dolphin (Stenella coeruleoalba) from the Bay of Biscay, France - S. Labrut; B. Thuillier; T. Khomasuridze; M. Prot; E. Simon-Lorière; S. Wund (Journal of Comparative Pathology, 2025)

Strengthening the health surveillance of marine mammals in the waters of metropolitan France by monitoring strandings - S. Wund; E. Méheust; C. Dars; W. Dabin; F. Demaret; B. Guichard; T. Jauniaux; S. Labrut; J. Spitz; O. Van Canneyt; F. Caurant (Frontiers in Marine Science, 2023)
Monitoring the health status of marine mammals is a priority theme that France aims to develop with the other European Union Member States in the next two years, in the context of the Marine Strategy Framework Directive. With approximately 5,000 km of coastline and for nearly ten years, France has been recording an average of 2,000 strandings per year, which are monitored by the National Stranding Network, managed by Pelagis, the observatory for the conservation of marine mammals from La Rochelle University and the French National Center for Scientific Research. Since 1972, this network has successively evolved from spatial and temporal faunistic description to, nowadays, the detection of major causes of mortality. It now aims to carry out epidemiological studies on a population scale. Thus, a strategy to strengthen the monitoring of marine mammals’ health status based on stranding data has been developed. This strategy will allow for a more accurate detection of anthropogenic cause of death as well as those of natural origin. It will allow the monitoring of time trends and geographical differences of diseases associated with conservation and public health issues while ensuring the early detection of emerging and/or zoonotic diseases of importance. It will also allow a better assessment of the consequences of human activities on these animal populations and on the environment. Thus, this strategy is fully in line with the “One Health” approach which implies an integrated vision of public, animal and environmental health. It is broken down into four surveillance modalities: (1) general event-based surveillance (GES); (2) programmed surveillance (PS); (3) specific event-based surveillance (SES); (4) and in the longer term, syndromic surveillance (SyS). This article describes the French strategy as well as these different surveillance modalities, the levels of examinations and the associated sampling protocols and finally, the method of standardisation of the data collected. The objective is to present the strategy developed at the French level in order to integrate it into a future strategy shared at the European level to standardise practices and especially complementary analysis, necessary for a better evaluation of the health status of these mobile marine species.

Molecular identification of iridoviruses infecting various sturgeon species in Europe - L Bigarré; M Lesne; A Lautraite; V Chesneau; A Leroux; M Jamin; P M Boitard; A Toffan; M Prearo; S Labrut; P Daniel (Journal of Fish Diseases, 2017)
Iridoviridae are known to cause disease in sturgeons in North America. Here, histological and molecular methods were used to screen for this family of virus in sturgeons from various European farms with low‐to‐high morbidity. Some histological samples revealed basophilic cells in the gill and labial epithelia, strongly suggesting the accumulation of iridovirus particles. Newly developed generic PCR tests targeting the major capsid protein ( MCP ) gene of sturgeon iridoviruses identified in North America, namely the white sturgeon iridovirus and the Namao virus ( NV ), produced positive signals in most samples from four sturgeon species: Russian ( Acipenser gueldenstaedtii ), Siberian ( A. baerii ), Adriatic ( A. naccarii ) and beluga ( Huso huso ). The sequences of the PCR products were generally highly similar one another, with nucleotide identities greater than 98%. They were also related to (74–88%), although distinct from, American sturgeon iridoviruses. These European viruses were thus considered variants of a single new virus, provisionally named Acipenser iridovirus‐European (Ac IV ‐E). Moreover, three samples infected with Ac IV ‐E showed genetic heterogeneity, with the co‐existence of two sequences differing by five nucleotides. One of our European samples carried a virus distinct from Ac IV ‐E, but closely related to NV identified in Canada (95%). This study demonstrates the presence of two distinct sturgeon iridoviruses in Europe: a new genotype Ac IV ‐E and an NV ‐related virus.

First detection of Cyprinid Herpesvirus 2 (Cy HV ‐2) in goldfish ( Carassius auratus ) in France - P‐M Boitard; M Baud; S Labrut; C de Boisséson; M Jamin; L Bigarré (Journal of Fish Diseases, 2016)
Massive mortalities of Carassius auratus (L.) occurred in a farm in France during summer 2014. Fish presented anorexia, loss of scales and large amounts of mucus on the gills. Necrosis of the distal tip of the filament and the lamellae, combined with fusion of the lamellae, was observed, as well as necrosis in the hematopoietic organs and in the digestive tract. The histological examination led to hypothesize the implication of a virus in the mortality. The presence of cyprinid herpesvirus 2 (Cy HV ‐2) in dead fish was demonstrated by amplification and sequencing of portions of the DNA polymerase and helicase genes, both sequences exhibiting 100% identity with Cy HV ‐2 from Japan. In an attempt to find genetic markers of variation, two regions containing tandem repeats in the Japanese genome were amplified from a virus‐positive sample from the present outbreak. A first region ( mB ) was fully identical to the Japanese isolate. However, the second region ( mA ) exhibited a range of deletions and substitutions compared to Cy HV ‐2 from Japan. This is the first report of Cy HV ‐2 in France in association with mortality of goldfish and the first identification of a molecular marker for its tracing.